An insight of mucormycosis (black fungus) in ayurveda - Mohsina FP; Faheem IP; Tabassum S; Shah I; Ahmad A (Open Journal of Pharmacology and Pharmacotherapeutics - Peertechz Publications, 2021)
Mucormycosis, commonly known as black fungus, is a rare but serious fungal infection caused by a fungus called Mucormycete, which is abundant in the environment. It mainly affects people with preexisting diseases or people taking medications that reduce the body's ability to fight infections and disease. It is detected relatively frequently in COVID19 patients in several states of India. The disease usually manifests on the skin and also affects the lungs and brain. People who are suffering from COVID- 19 and who are in recovery stage have a poor immunity and take the prevalence of disease higher and hence the immune system won't develop sufficient antibodies to fight against them. People hospitalized with severe COVID19 illness who were prescribed with steroids to reduce the infection. Steroids work by reducing inflammation in the lungs and reducing the body's immune response to prevent it from attacking healthy cells in the body, resulting in a decreased ability to monitor immune responses. These patients are very sensitive to the effects of Mucormycete. This infection will not spread from person to person. This infection starts first in the nose and spreads to the eyes, then to the lungs and brain. This black fungus is now seen more frequently in post COVID19 Patients in India specifically. The present review is based over the ayurvedic treatment under AYUSH used for the black fungus infection.